Breeding goats for intensive management - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1991)
Traditionally goats have been herded or allowed to roam free range. Their high reproductive performance and ability to survive and even thrive on poor quality feeds not generally eaten by other species has made them attractive to resource-poor...